2017
DOI: 10.3892/mmr.2017.6403
|View full text |Cite
|
Sign up to set email alerts
|

Role of autophagy in advanced atherosclerosis

Abstract: Abstract. Atherosclerosis (AS) remains the leading cause for global cardiovascular disease morbidity and mortality, and a major cause of cardiopathy, myocardial infarction and peripheral vascular diseases. Macrophages serve a critical role in atherosclerotic plaque stabilization and rupture, and the selective removal of macrophages may be beneficial in improving plaque stability. Autophagy is a process of self-feeding, during which cytoplasmic proteins or organelles are packaged into vesicles and fused with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…6 Mounting evidence have indicated that autophagy has a promising potential as diagnostic and prognostic indicators in various diseases containing atherosclerosis. 7 Lipoautophagy, a type of autophagy that delivers lipid droplets (LDs) for degradation and regulates lipid metabolism, is involved in the process of atherosclerosis. 8 Activation of autophagy by intercellular and/or extracellular stimuli protects macrophage cells against cell apoptosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Mounting evidence have indicated that autophagy has a promising potential as diagnostic and prognostic indicators in various diseases containing atherosclerosis. 7 Lipoautophagy, a type of autophagy that delivers lipid droplets (LDs) for degradation and regulates lipid metabolism, is involved in the process of atherosclerosis. 8 Activation of autophagy by intercellular and/or extracellular stimuli protects macrophage cells against cell apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy is an evolutionary conserved metabolic process in which denatured proteins and damaged organelles are degraded through the lysosomal system for the maintenance of intracellular homeostasis during various stress conditions . Mounting evidence have indicated that autophagy has a promising potential as diagnostic and prognostic indicators in various diseases containing atherosclerosis . Lipoautophagy, a type of autophagy that delivers lipid droplets (LDs) for degradation and regulates lipid metabolism, is involved in the process of atherosclerosis .…”
Section: Introductionmentioning
confidence: 99%
“…In fact, autophagy is involved in multiple processes of carotid plaque formation and differentiation, and may constitute a protective mechanism to promote cell survival in the plaque [29,37]. Current research indicates that autophagy becomes dysfunctional during the progression of atherosclerosis, and that this process affects the main cellular constituents of the plaque differently [38,39]. Plaque-associated macrophages respond to autophagy impairment by undergoing apoptosis, while VSMCs engage the senescence program, with both phenomena shown to promote plaque progression [39].…”
Section: Discussionmentioning
confidence: 99%
“…Previous study has reported that plaque necrosis in advanced atherosclerosis might be due to the defects in clearing apoptotic macrophage cells which results in atherosclerotic cardiovascular events [27]. Autophagy is another biologically conservative process that plays an important role in maintaining lipid metabolism and apoptosis in obesity and atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%